Lean Manufacturing and Process Optimization : Enhancing Efficiency in Modern Production - Sujata Sujeet Dutta, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the transformative impact of lean manufacturing and process optimization in modern industrial settings. It delves into these methodologies' principles, tools, and benefits, highlighting their crucial role in enhancing operational efficiency, reducing costs, and improving product quality. The article presents key statistics and case studies, including Japanese automotive manufacturer's benchmark lean manufacturing model, to demonstrate the significant improvements in productivity, quality, and cost-effectiveness achieved through these approaches. It also discusses the implementation strategies for lean and process optimization, emphasizing the importance of leadership commitment, employee training, and technology integration. Integrating Industry 4.0 technologies with lean principles, termed Lean 4.0, is introduced as the next frontier in operational excellence.
Keywords: Lean Manufacturing; Process Optimization; Operational Efficiency; Continuous Improvement; Industry 4.0